Formamidinium Lead Bromide (FAPbBr3) Perovskite Microcrystals for Sensitive and Fast Photodetectors - Zhang, Fengying; Yang, Bin; Zheng, Kaibo; Yang, Songqiu; Li, Yajuan; Deng, Weiqiao; He, Rongxing (Nano-Micro Letters, 2018)
Because of the good thermal stability and superior carrier transport characteristics of formamidinium lead trihalide perovskite HC(NH2)2PbX3 (FAPbX3), it has been considered to be a better optoelectronic material than conventional CH3NH3PbX3 (MAPbX3). Herein, we fabricated a FAPbBr3 microcrystal-based photodetector that exhibited a good responsivity of 4000 A W−1 and external quantum efficiency up to 106% under one-photon excitation, corresponding to the detectivity greater than 1014 Jones. The responsivity is two orders of magnitude higher than that of previously reported formamidinium perovskite photodetectors. Furthermore, the FAPbBr3 photodetector’s responsivity to two-photon absorption with an 800-nm excitation source can reach 0.07 A W−1, which is four orders of magnitude higher than that of its MAPbBr3 counterparts. The response time of this photodetector is less than 1 ms. This study provides solid evidence that FAPbBr3 can be an excellent candidate for highly sensitive and fast photodetectors. Highlights: 1 Formamidinium lead trihalide (FAPbBr3) microcrystal-based photodetectors facilitate efficient charge transfer. 2 The fabricated FAPbBr3 photodetector shows good responsivity, external quantum efficiency, and detectivity. 3 Two-photon performance of the photodetectors is better than that previously reported for MAPbBr3 photodetectors.